Formation of multimeric antibodies for self-delivery of active monomers. (1st January 2017) - Dekel, Yaron; Machluf, Yossy; Gefen, Tal; Eidelshtein, Gennady; Kotlyar, Alexander; Bram, Yaron; Shahar, Ehud; Reslane, Farah; Aizenshtein, Elina; Pitcovski, Jacob
Abstract: Proteins and peptides have been used as drugs for almost a century. Technological advances in the past 30 years have enabled the production of pure, stable proteins in vast amounts. In contrast, administration of proteins based on their native active conformation (and thus necessitating the use of subcutaneous injections) has remained solely unchanged. The therapeutic anti-HER2 humanized monoclonal immunoglobulin (IgG) Trastuzumab (Herceptin) is a first line of the treatment for breast cancer. Chicken IgY is a commercially important polyclonal antibody (Ab). These Abs were examined for their ability to self-assemble and form ordered aggregates, by several biophysical methods. Atomic force microscopy analyses revealed the formation of multimeric nanostructures. The biological activity of multimeric IgG or IgY particles was retained and restored, in a dilution/time-dependent manner. IgG activity was confirmed by a binding assay using HER2 + human breast cancer cell line, SKBR3, while IgY activity was confirmed by ELISA assay using the VP2 antigen. Competition assay with native Herceptin antibodies demonstrated that the binding availability of the multimer formulation remained unaffected. Under long incubation periods, IgG multimers retained five times more activity than native IgG. In conclusion, the multimeric antibody formulations can serve as a storage depositories and sustained-release particles. These two important characteristics make this formulation promising for future novel administration protocols and altogether bring to light a different conceptual approach for the future use of therapeutic proteins as self-delivery entities rather than conjugated/encapsulated to other bio-compounds.